Enhanced Circularly Polarized Green Luminescence Metrics from New Enantiopure Binary Tris-Pyrazolonate-Tb3+ Complexes - Liu, Jiaxiang; Zhang, Yongwen; Yao, Ruijuan; Ren, Haitao; Wang, Weijie; Feng, Haohao; Li, Wentao; Miao, Zongcheng (Molecules (Basel, Switzerland), 2024)
Achieving superior circularly polarized luminescence brightness (BCPL) is an important subject and continuous challenge for chiroptical materials. Herein, by applying a binary molecular design for the synthesis of chiral organo-Tb3+ molecules, a novel pair of mononuclear chiral tris-pyrazolate-Tb3+ enantiomers, [Tb(PMIP)3(R,R-Ph-PyBox)] (2) and [Tb(PMIP)3(S,S-Ph-PyBox)] (5), have been synthesized and characterized. The three 1-phenyl-3-methyl-4-(isobutyryl)-5-pyrazolone (HPMIP) ligands play the role of efficient luminescence sensitizers and strong light-harvesting antennas, while the enantiopure 2,6-bis(4-phenyl-2-oxazolin-2-yl) pyridine ligand (R,R/S,S-Ph-PyBox) is employed as the strong point-chiral inducer. With the proper combination of the HPMIP and Chiral-Ph-PyBox within the Tb3+ enantiomers, strong (PMIP)−-centered π-π* electronic absorption (ε263 nm = 38,400–39,500 M−1 cm−1) and brilliant high-purity ligand-sensitized Tb3+-centered green luminescence (ΦPL = 47–48%) were observed. In addition, a clear circularly polarized luminescence (CPL) activity (|glum| = 0.096–0.103) was also observed, resulting in a strong BCPL (610–623 M−1 cm−1) for the two Tb3+ enantiomers from the hypersensitive transitions. Our results offer an effective path to develop high-performance chiroptical organo-Tb3+ luminophores.